Manufacture aluminum alloy tube from powder with a single-step extrusion via ShAPE. (August 2022) - Li, Xiao; Wang, Tianhao; Ma, Xiaolong; Overman, Nicole; Whalen, Scott; Herling, Darrell; Kappagantula, Keerti
Abstract: The mechanical performance of aluminum (Al) in terms of strength, wear, and corrosion resistance, especially high-temperature strength, has been shown to improve with the addition of transition metal (TM) elements of Fe, Cr, and Ti. However, the feedstock of Al-TM alloy occurs as powders. Making extrudate from powders requires multiple procedures and consumes considerable energy. This study developed Shear Assisted Processing and Extrusion (ShAPE) as a single-step process that manufactures tubes directly from Al-TM powders obtained via gas atomization. Meter-long Al-TM alloy tubes are extruded from powders with different processing conditions. The average density of ShAPE tubes is 2.94 kg/cm 3, equal to or higher than parts fabricated by hot extrusion and sintering. The powder-to-tube fabrication process was revealed and discussed by examining the microstructural evolution. The Vickers hardness of ShAPE tubes ranges from 110 to 140 HV through the wall thickness and at different extrusion speeds. The variation in hardness was correlated with the extent of refinement of intermetallics and attributed to the shear deformation per unit extrusion length. Energy cost analysis shows that ShAPE saves about 60 % energy compared to the traditional sintering and extrusion processes. Results indicate ShAPE is a low-cost, high-efficiency manufacturing process for producing tubes from metallic powders. Highlights: Developed ShAPE as a single-step process that manufactures tubes directly from Al-transition metal powders. Revealed the powder-to-tube fabrication process by examining the microstructural evolution. Correlated hardness variation with the size of intermetallics and extent of the shear deformation. Energy cost analysis shows that ShAPE saves 60% energy compared to the traditional sintering and extrusion processes.